Antioxidant activity against H2O2-induced cytotoxicity of the ethanol extract and compounds from Pyrola decorate leaves. (1st January 2017) - Yang, Xiliang; Peng, Qingyun; Liu, Qian; Hu, Jie; Tang, Zhipeng; Cui, Lianjie; Lin, Zonghao; Xu, Bing; Lu, Kuojian; Yang, Fang; Sheng, Zhizheng; Yuan, Qiong; et al.
Abstract: Context: The leaves of Pyrola decorate H. Andr (Pyrolaceae), known as Luxiancao, have long been used for treating kidney deficiency, gastric haemorrhage and rheumatic arthritic diseases in traditional Chinese medicine. Objective: The phytochemicals and antioxidant capacities in vitro of P. decorate leaves were investigated. Materials and methods: Ethanol, petroleum ether, acetidin, n -butyl alcohol and aqueous extracts of Pyrola decorate leaves were prepared by solvent sequential process, and then isolated and purified to obtain phytochemicals. Cell viability was measured by MTT assay. PC12 cells were pretreated for 24 h with different extractions of P. decorate leaves at concentrations of 0.1, 0.5, 1, 5 and 10 mg/mL, then H2 O2 of 0.4 mM was added in all samples for an additional 2 h. The antioxidant capacities of betulin, ursolic acid and monotropein were determined in PC12 cells against H2 O2 induced cytotoxicity in vitro as well. Results: Nine compounds (1 –9 ) were isolated and structurally determined by spectroscopic methods, especially 2D NMR analyses. Ethanol extract treated groups showed inhibitory activity with IC50 value of 10.83 mg/mL. Betulin, ursolic acid and monotropein were isolated from P. decorate, and demonstrated with IC50 values of 6.88, 6.15 and 6.13 μg/mL, respectively. Discussion and conclusions: In conclusion, Pyrola decorate is a potential antioxidative natural plant and worth testing for further pharmacological investigation in the treatment of oxidative stress related neurological disease.